An overview of the economic importance and control of termites in plantation forestry and wood preservation in Peninsular Malaysia - Kirton, Laurence G.; Wong, Andrew H.H; Kee, Suan Cheok (IRGWP, 2000)
Both the plantation forestry and wood preservation industries in the tropical and subtropical belts of the world, exemplified by the humid equatorial Peninsular Malaysia, regard termites as major destructive pests of standing trees, various timber products and building timber structures. This paper is a compilation of information on these economically important structural pests encountered in both plantation forestry and the wood preservation industry in Malaysia, particularly the peninsula, and describes ongoing termite research activities to establish practical control strategies for tree and wood protection.